GE_GERICHTE P/16453/2012 vom 3. Oktober 2013 - GE Cour de justice (2013)
MENDICITÉ; DISCRIMINATION RACIALE; LIBERTÉ D'EXPRESSION; AUTORISATION DE SÉJOUR; SÉJOUR ILLÉGAL | CEDH.10.1; CEDH.10.2; Cst.8.2; LPG.11A; LEtr.10; LEtr.115.1; RTP.1.1; RTP.1.3; RPSS.4